Acoustic parameters of sound insulating materials investigation in small reverberation rooms on rubber plates - Вишневський, О.А. (Proceedings of National Aviation University, 2005)
The mathematical model of the mean loading allocated along the arc of a touch of a roller and a sample is submitted. The mean contact area of the roller and the sample and the mean loading during realization of the experiment is defined. The generalized model of an abrasive wear of surfaces of materials is constructed, at not hard-mounted abrasive particles.